Maturation of circulating Ly6ChiCCR2+ monocytes by mannan-MOG induces antigen-specific tolerance and reverses autoimmune encephalomyelitis - Dagkonaki, Anastasia; Papalambrou, Athina; Avloniti, Maria; Gkika, Areti; Evangelidou, Maria; Androutsou, Maria-Eleni; Tselios, Theodore; Probert, Lesley (Frontiers in Immunology, 2022)
Autoimmune diseases affecting the CNS not only overcome immune privilege mechanisms that protect neural tissues but also peripheral immune tolerance mechanisms towards self. Together with antigen-specific T cells, myeloid cells are main effector cells in CNS autoimmune diseases such as multiple sclerosis, but the relative contributions of blood-derived monocytes and the tissue resident macrophages to pathology and repair is incompletely understood. Through the study of oxidized mannan-conjugated myelin oligodendrocyte glycoprotein 35-55 (OM-MOG), we show that peripheral maturation of Ly6ChiCCR2+ myeloid precursors to Ly6ChiMHCII+PD-L1+ cells is sufficient to reverse spinal cord inflammation and demyelination in MOG-induced autoimmune encephalomyelitis. Soluble intradermal OM-MOG drains directly to the skin draining lymph node to be sequestered by subcapsular sinus macrophages, activates Ly6ChiCCR2+ monocytes to produce MHC class II and PD-L1, prevents immune cell trafficking to spinal cord, and reverses established lesions. We previously showed that protection by OM-peptides is antigen specific. Here, using a neutralizing anti-PD-L1 antibody in vivo and dendritic cell-specific Pdl1 knockout mice, we further demonstrate that PD-L1 in non-dendritic cells is essential for the therapeutic effects of OM-MOG. These results show that maturation of circulating Ly6ChiCCR2+ monocytes by OM-myelin peptides represents a novel mechanism of immune tolerance that reverses autoimmune encephalomyelitis.